The Moderating Role of Religiosity and Ethics Education on The Relationship Between Fraud Diamond Dimensions and Machiavellian Traits in Academic Fraud - Waworuntu, Rizky Kurniawan; Yudhi Fahrianta, Riswan; Ramaraya Koroy, Tri; Yafiz Syam, Akhmad (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study investigates the influence of the fraud diamond elements and Machiavellian traits on academic fraud, with religiosity and ethics education serving as moderating variables. Primary data were collected through questionnaires from 192 undergraduate students at the Institut Bisnis & Teknologi Kalimantan and Universitas Lambung Mangkurat. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that rationalization, capability, and Machiavellianism have significant effects on academic fraud, while pressure and opportunity do not. However, the patterns vary across institutions, highlighting that the influence of preceding factors is contextual. Furthermore, both religiosity and ethics education fail to serve as consistent and effective preventive measures, suggesting that these values have not been fully internalized by students. This study contributes by revealing the nuanced and contextual nature of factors leading to fraud and the limitations of conventional value-teaching methods in higher education.